(untitled) (Economia Aplicada, 2001)
This paper argues that, contrary to the trend in the Metropolitan Region ofthe State of São Paulo, the interior of the State is managing to increase its share of the country's manufacturing employment because of successful industrial clusters. On the basis of an index of pecialization, the paper identifies a number of clusters and selects a few ofthem for comments in the light of existing theoretical approaches. Finally, policy implications and possibilities forjoint action by local economic agents and institutions are discussed, taking into account the existing constraints for national industrial policy-making. The outcome points out that industrial clusters in the interior of São Paulo State are characterized by their diversity in terms of history, morphology, industrial organization, local supporting institutions, social and cultural contexts and public policies. To recognize the relevance of this diversity is the first and most important step for designing any policy or joint action initiatives.